Assessing the quality of life of people with diabetes in a hospital in Takoradi-Ghana - Agyei, Kofi G.; Anderson, Seida E.; Avege, Nora S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Persons living with diabetes have been shown to have a significant negative impact on both their physical and mental wellbeing. This study sought to determine the quality of life of people with diabetes. Methods: A descriptive study was used for this study. A convenient sampling technique was employed to recruit 100 participants at the Nagel Adventist Memorial hospital in Ghana. The instrument that was used to collect data from participants was a questionnaire adopted from the MDQoL-17 questionnaire. Results: The study showed that a majority of the participants 60% indicated that, they were very satisfied with their treatment at NMAH. In addition, 36% indicated they were moderately satisfied and just 4% indicated they were not satisfied with the treatment at all. Seventy- eight percent (78%) representing the majority of participants indicated they get physically ill and had poor physical functions. A p value of 0.428 was recorded for an association between gender and treatment satisfaction with a Cramer V value of 0.148. Conclusions: The study found no significant association between gender, age and quality of life. Also, the participants recruited was found to have a poor quality of life. The study therefore suggests that Stakeholders and Ministry of Health should subsidize the cost of treatment or even make diabetes medications free to enable everybody get access to it and also health facilities should inculcate physical and psychological training into their diabetes education to help improve patients’ quality of life.